Peran Kepemimpinan Kepala Sekolah Dalam Lembaga Pendidikan Islam di MTs Al-Jihad Medan - Akmalia, Rizki.; Syahkila, Arimbi; Situmorang, Mela Safitri; Dahyanti, Nur; Harahap, Tri Suci Apriani; Ramadhan, Syahpan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this research is to explain the leadership of the principal at MTS AL-JIHAD MEDAN, the method used in this research is descriptive research using qualitative. Data obtained from interviews, observation and documentation. These results find that leadership and education are two different things. Leadership itself means a main object that has influence on other objects, while education is an effort to create a learning atmosphere and learning process so that students are able to absorb or get something new, whether in the form of knowledge and experience. On this occasion we will discuss leadership in integrated Islamic school education institutions. In an Islamic educational institution at Mts Al Jihad Medan. Leadership plays an important role and has a great responsibility, because it is the prime mover and also a motivator for the organization they lead. In the leadership system, it must have its own role in order to facilitate the pace of movement of its leadership and also to facilitate the achievement of the vision and mission of the leadership. Leadership will be said to be successful if the rate of leadership is directed according to the initial goals of the organization. So these two things between leadership and education are important and interesting things for us to discuss thoroughly, so that we can also have attitudes and knowledge like a leader, especially in the world of education. Keywords: Of principal leadership, islamic educational instituons